Women’s language features: Identifying language and gender in a talk show from a sociolinguistics the perspective - Purba, Ridwin; Saddhono, Kundharu; Herman, Herman; Widodo, Arif; Risdianto, Faizal; A, Fatmahwati; Saputra, Nanda (Research Journal in Advanced Humanities, 2023)
This study aimed to identify the kinds and purposes of women’s language used by Cinta Laura in talk shows. To address the research issue, the researchers utilized a qualitative research approach and content analysis. The researchers as the human research subjects and the observation sheet were the two research tools used in this study. The researchers used Cinta Laura’s talk show recording and video script, which she presented in June 2021, to conduct their study. This study’s findings indicated that not all forms of women’s language employed Cinta Laura. The researchers identified seven different gender-specific linguistic features. Lexical hedges account for 24.90% of these characteristics, rising intonation for 1.28, empty adjectives for 1.16, intensifier for 22.56, hypercorrect grammar for 32.29, avoidance of harsh swearing for 0.3%, and emphatic stress for 15.95%. Tag inquiry, price color word, and extreme politeness are characteristics of the language of the absent ladies. Hypercorrect grammar is the language trait most common in women. Hypercorrect grammar in this Talk Show serves to highlight the key concept or term that she wished to accentuate.